A Study of Dangme Adverbs and Adverbials - Asamoah, Y.D. (University Of Ghana, 2018)
This study investigated the nature of adverbs and adverbials in Dangme (Kwa, Niger-Congo). It looked at the morphological, semantic and syntactic properties exhibited by Dangme adverbs. Data for the study were gathered from books and recordings of free oral utterances of native speakers. Using functional grammar and its prototypical means of categorization as the theoretical framework of this study, adverbs and adverbials were identified and analysed. The finding showed that in Dangme, adverbial concepts are expressed not only by prototypical adverbs but also by derived elements, temporal nouns, adjectives and emphatic markers. The class ‘adverbs’ was also shown to be connected with other higher syntactic constituents termed ‘adverbials’. Dangme does not have affixes for the derivation of adverbs; however it does so through reduplication and compounding. The study also revealed that an adverb/adverbial in Dangme falls into six major semantic classes, namely; manner, time, place, aspectual, epistemic and contingency. The study showed that syntactically, an adverb in Dangme may be either a Sentence adverb or VP-adverb and revealed that the distribution and sequencing of adverbs/adverbials are influenced by the meanings of the adverbs themselves and their scope capabilities.
MPhil.
Keywords: Dangme; Adverbs; Adverbials